Rancang Bangun Generator Listrik Dengan Pole Modulator Sebagai Induktor Torsi Balik Yang Ditimbulkan Oleh Back Emf - Normansyah Normansyah (entries, 2022)
This study relates to a reverse current electric generator or commonly known as an AC generator. ( alternating current). AC generators are widely known in the electrical world. All power generators require increased activation power due to the electrical load on the generator. In other words, with the increasing load applied to the generator, the more power is needed by its drivers, whether the energy source is oil, water, wind or other.The research on this final project aims to reduce the power increases required by the drill resulting from the increase of the electrical load on the generator so that it can result in efficiency and reduce the cost of producing electrical energy on such generator.To avoid changes that cause the induction style by providing the opposing magnetic field or re-inducing the reverse electrical motion style or the Back EMF to the generator gear to be able to reduce the required initial torque so that it can reduce the power required by the driver along with the addition of load on the Generator. This can reduce the cost of generating electricity from the generator. As for the initial design of the specification of this generator, the outer power is 2,200 watts, the induction voltage is 220 volts, 1 phase, the frequency is 50 Hz, the rotation speed of the generator is 375 rpm.